PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, UKURAN PERUSAHAAN, PERUBAHAN ARUS KAS OPERASI DAN MARKET TO BOOK RATIO TERHADAP EARNINGS MANAGEMENT PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - AYU SANTOSO, ANGGARDINI (Jurnal Akuntansi AKUNESA, 2017)
The purpose of this research is to analyze the effect of managerial ownership, leverage, firm size, change of operating cash flow and market-to-book ratio affecting earnings management at manufacturing companies listed on Indonesia Stock Exchange from 2011 until 2015.Using multiple regression technique, this research shows that managerial ownership, leverage, and operating cash flow changes have no significant effect on companies’ earnings management. Meanwhile, firm size and market to book ratio have significant effect on companies’ earnings management.   Keywords: Change of Cash Flow Operation, Company Size, Managerial Ownership, Earnings Management,  Leverage, Market to Book Ratio